Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1991
DOI: 10.1210/jcem-73-1-18
|View full text |Cite
|
Sign up to set email alerts
|

Mitotane Enhances Cytotoxicity of Chemotherapy in Cell Lines Expressing a Multidrug Resistance Gene (mdr-1/P-Glycoprotein) which is also Expressed by Adrenocortical Carcinomas

Abstract: P-Glycoprotein (Pgp), product of the mdr-1 gene, is a 130- to 180-kDa plasma membrane phosphoglycoprotein which mediates multidrug resistance in cell culture by increasing efflux of the natural product chemotherapeutic agents. High levels of expression of mdr-1/Pgp are found in both the normal adrenal and adrenocortical cancers. By RNA in situ hybridization the expression in adrenocortical cancer is shown to be widely distributed. The present study demonstrates that decreased drug accumulation mediated by mdr-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0
4

Year Published

1993
1993
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(59 citation statements)
references
References 32 publications
1
54
0
4
Order By: Relevance
“…16,17 Furthermore, in vitro studies with the ACC cell line, H295, have demonstrated high levels of Pgp expression with evidence of a role for this protein in mediating drug efflux. 18 The high levels of Pgp expression and its demonstrated function as a drug efflux pump suggests that the treatment of ACC may benefit from the addition of a Pgp antagonist. Previous studies have shown that in vitro, mitotane can increase drug accumulation by decreasing drug efflux, resulting in enhanced cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16,17 Furthermore, in vitro studies with the ACC cell line, H295, have demonstrated high levels of Pgp expression with evidence of a role for this protein in mediating drug efflux. 18 The high levels of Pgp expression and its demonstrated function as a drug efflux pump suggests that the treatment of ACC may benefit from the addition of a Pgp antagonist. Previous studies have shown that in vitro, mitotane can increase drug accumulation by decreasing drug efflux, resulting in enhanced cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…This effect has been observed in cell lines expressing Pgp, suggesting that mitotane interferes with Pgp function. 18,19 The current report describes the results of a Phase II study evaluating a multimodality approach in patients with metastatic ACC. The treatment strategy was comprised of daily mitotane (o.p.ЈDDD) with continuous infusion doxorubicin, vincristine, and etoposide that was administered preoperatively and postoperatively to patients with potentially resectable disease.…”
mentioning
confidence: 99%
“…Finally, the possible interactions of mitotane with other antitumor agents, including the chemotherapeutic drugs commonly used for ACC treatment, are poorly explored. In this latter respect, mitotane has been shown to sensitize ACC cancer cells to ionizing radiation (Cerquetti et al, 2008) and to enhance cytotoxicity of chemotherapy by reversing P-glycoprotein-mediated multidrug resistance with a specific effect on the cell cycle (Bates et al, 1991). However, very few studies determined in vitro the activity of mitotane in combination with other chemotherapeutic agents used in ACC patients (Villa et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Chemotherapy in combination with mitotane was used fol-lowing the concept that mitotane inhibits the MDR-1/Pglycoprotein, a multidrug resistance protein functioning as a drug efflux pump, widely expressed in ACC [148]. Chemotherapy drugs used alone or in combination in the treatment of advanced ACC patients include cisplatin, etopo-side, doxorubicin/adriamycin, vincristine, 5-fluorouracil, and streptozotocin [89,133,149,150].…”
Section: Chemotherapymentioning
confidence: 99%